A Study on Cancer Related Fatigue and Quality of Life (QOL) among Women Undergoing Treatment for Various Cancers in Selected Tertiary Care Hospitals of Ludhiana, Punjab - Maninderjit Kaur; Nidhi Sagar; Mamta (International Journal of Oncological Nursing and Practices, 2023)
Cancer is a collection of illnesses marked by irregular cell proliferation that has the potential to infiltrate or metastasize to different areas of the body. Gynecological cancer specifically refers to the abnormal cell growth in the female reproductive tract, including various organs such as the endometrium, fallopian tubes, ovaries, uterus, cervix, vagina, and breast. These cancer cells have a tendency to multiply uncontrollably. The majority of individuals diagnosed with cancer experience cancer-related fatigue at some point during their illness, which is a common and distressing symptom. This fatigue has a significant impact on patients, affecting their physical capabilities, emotional state, and overall well-being. One of the most frequent reported side effects across all types and stages of the disease is cancer-related fatigue. Factors that perceived to affect the women fatigue are physical, mental, emotional, social and spiritual factors and these ultimately affect their quality of life too. The objective is to evaluate the level of cancer-related fatigue and the quality of life in women receiving treatment for different types of cancer, with the aim of enhancing their overall welfare. A quantitative research approach and cross-sectional research design was used including 100 women with cancer visiting American Oncology Institute DMCH and Mohan Dai Oswal Cancer Hospital, Ludhiana, Punjab. Data was collected by using purposive sampling technique. FACIT (Functional Assessment of Chronic Illness Therapy) Fatigue Scale (version 4) by S. Acaster, 2015 was used to assess Cancer Related Fatigue and FACT-G (Functional Assessment of Cancer Therapy-General) Scale (version 4) by Dr. David Cella, 1993 was used to assess Quality of Life among women with various cancers. Interviews were conducted to collect quantitative data, which was then organized in a tabular format. Statistical analysis, both descriptive and inferential, was conducted using SPSS version 16 software. The findings of the study indicated that a majority of women (56%) fell within the age range of 51–60 years. All women were married and had children. Majority of women (41%) had 31–40 years of duration of marriage. Most of the women (53%) belonged to Sikh religion followed by 47% belonged to Hindu religion. Less than half (33%) of women were graduate and above. Majority of women (87%) were housewives whereas 13% were doing job/business. Maximum of women (57%) were living in the nuclear family and belonged to urban (56%) areas. Maximum of women (82%) were vegetarian and more than half (55%) of women belonged to upper middle class. Mean age score was found to be 52.43±8.10 years among women. The study concluded that all the women had cancer related fatigue. There was association of cancer related fatigue and quality of life with selected socio-demographic variables and also association was found between cancer related fatigue and quality of life.
Keywords: Cancer related fatigue; FACIT Fatigue Scale; FACT-G Scale; gynecological cancer